The "GURILAPS" Integrated Tourism Policy Evaluation: Breaking Indonesia's Metropolitan Monopoly Through a Mixed Methods Revolution - Gunawan Undang Undang; Diki Suherman; Deden Suhendar; Dina Dina; Diah Apriliani; Eny Nuryani Resmiawati (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
Regional development disparities between metropolitan and rural areas in West Java are intensifying, particularly impacting Southern West Java (SWJ) despite its significant tourism potential, meanwhile, the Western (WWJ), Central (CWJ), and Northern (NWJ) regions of West Java have experienced rapid progress. This study aims to evaluate regional planning policies for integrated tourism development through the "GURILAPS" (Gunung, Rimba, Laut, Pantai, Seni & Budaya) Framework — Mountains, Jungle, Ocean, Water, Beaches, Arts & Culture. The methodology employs a QUAN → qual design, analyzing built-up area expansion data (2010-2024) from BPS through ANOVA and trend analysis, followed by thematic analysis of stakeholder sources and 28 policy documents. Quantitative findings reveal significant disparities: WWJ, CWJ, and NWJ experienced 21.4% built-up area growth (2010-2024), while SWJ achieved only 11.8% (F(5,21) = 24.67, p < 0.001, η² = 0.855). Qualitative findings identified four themes: infrastructure connectivity gaps, institutional coordination limitations, community tourism readiness challenges, and policy implementation gaps. The validated "GURILAPS" Framework (Content Validity Index: 0.89, Inter-rater Agreement: Kappa = 0.82) provides a systematic approach to leveraging SWJ's natural and cultural assets while addressing infrastructure gaps and promoting rural economic growth. This research contributes theoretically through the validated "GURILAPS" Framework and methodologically by applying sequential explanatory mixed methods in tourism policy evaluation. Theoretical implications include the GURILAPS Framework, mixed methods innovation, and regional development theory advancement. Practical implications provide actionable evidence for policymakers, adaptable to other regions with similar characteristics, and applicable to developing countries facing comparable challenges.